Authentic Content-Based Instruction in EFL Classrooms: Preparing University Students for Real-World Communication - Rasmah N; Ayu Ashari; Emelia Fitri Limchio Sinaga; Zulkifli Surahmat; Markuna; Rahmaniar (Universitas Islam Negeri Palopo, 2026)
This study examines the effectiveness of Authentic Content-Based Instruction (CBI) in enhancing university students’ English communication skills and their readiness for real-world communication. It addresses two research questions: whether authentic CBI leads to greater improvement in communication performance compared to conventional instruction, and how students perceive its relevance to real-world contexts. A quasi-experimental design was employed involving 50 undergraduate students divided into experimental and control groups. Data were collected through pre-test and post-test assessments, questionnaires, and supporting qualitative insights, and analyzed using paired and independent sample t-tests alongside effect size estimation. The results indicate that while both groups improved, the experimental group achieved substantially higher gains, with mean scores increasing from 65.21 to 82.45, compared to 64.87 to 72.13 in the control group, reflecting a large effect. Students also reported higher engagement, stronger perceived authenticity, and greater communication readiness. These findings demonstrate that integrating authentic materials and task-based activities fosters meaningful language use and accelerates communicative competence. The study advances Content-Based Instruction by positioning authenticity as a core pedagogical element and provides practical guidance for designing context-driven, real-world-oriented EFL instruction in higher education.